Belly Bellows - Orojide-Isola, Akinwumi (University Press Plc, 2009)
This book attempt at recreating the popular Yoruba myth with a metaphor that gives a deeper understanding of individuals and groups in situations of conflict and cooperation.
Keywords: Plays